The Quarry Outside My Window: Geographies of Protest in Sochi 2014 - Wolfe, Sven Daniel (My University, 2025)
Every four years, the Winter Olympics become a focal point for activism and resistance. But in the modern era, mere bids to host the Games have sparked fierce opposition from groups motivated by local or global concerns. Russell Field edits a collection that charts the evolution of protest around the Winter Games and illuminates the issues at the heart of anti-Olympic activism. The essays collectively explore the shifting dynamics and power relations between the civic coalitions that pursue the Winter Olympics and the social movements that oppose their efforts. The contributors look at specific Games impacted by dissent and probe the issues that swirled around failed and withdrawn bids. In addition, contributions on the contemporary Olympics describe current or future bids while delving into the campaigns demanding host nations pay attention to economic, social, humanitarian, and environmental concerns. A first-of-its-kind collection, Winters of Discontent profiles the wide range of activists and social movements that have organized against the Winter Olympics.